Decision Support System for increasing position of Office at PT. Gramedia Asri Media using Profile Matching Method - Mariskhana, Kartika; Sintawati, Ita Dewi; Widiarina, Widiarina; Rusdiansyah, Rusdiansyah (Politeknik Ganesha Medan, 2021)
The more rapid growth of information technology in the world, so that more and more people are taking advantage of this advancement in information technology in various activities of life or to solve various problems. One of them is filling positions that have not been filled for promotion processes often experience problems because the submission of prospective candidates who can occupy the position by matching employee profiles and job profiles is not resolved properly. To minimize these constraints, a decision support system is needed that can analyze employee performance in accordance with existing job profiles. The Profile Matching process is carried out to determine career planning recommendations by calculating sub-criteria from each aspect (work attitude and intellectual capacity) which consists of 4 stages including the calculation of the GAP value, the calculation of the core and secondary factor values ​​and the calculation of the total value and ranking. The results of this study will produce a form in the form of employee recommendations with the highest score of 5.4163 on behalf of Ariz and Widi which has the same numerical value as the number from the calculation method used.